2023
DOI: 10.3390/ijms24054677
|View full text |Cite
|
Sign up to set email alerts
|

Heteromerization of Dopamine D2 and Oxytocin Receptor in Adult Striatal Astrocytes

Abstract: The ability of oxytocin (OT) to interact with the dopaminergic system through facilitatory D2-OT receptor (OTR) receptor-receptor interaction in the limbic system is increasingly considered to play roles in social or emotional behavior, and suggested to serve as a potential therapeutic target. Although roles of astrocytes in the modulatory effects of OT and dopamine in the central nervous system are well recognized, the possibility of D2-OTR receptor-receptor interaction in astrocytes has been neglected. In pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 129 publications
0
1
1
Order By: Relevance
“…3e-h). Our current data does not distinguish whether these results are due to loss of direct action of dopamine on striatal astrocytes or indirectly through known changes in local neuronal function and synaptic inputs [48][49][50] . Striatal astrocytes express dopamine receptors in their distal processes, potentially within the range of neuronal synapses [2][3][4] .…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…3e-h). Our current data does not distinguish whether these results are due to loss of direct action of dopamine on striatal astrocytes or indirectly through known changes in local neuronal function and synaptic inputs [48][49][50] . Striatal astrocytes express dopamine receptors in their distal processes, potentially within the range of neuronal synapses [2][3][4] .…”
Section: Discussioncontrasting
confidence: 58%
“…Locomotion in the open field is driven partly by exploration and subsides as animals habituate to the novel environment 49 . In agreement with previous work demonstrating that dopamine signaling is important for exploratory behavior 51 , we found that lesioned animals showed a pronounced deficit in the early phase of the open field when the exploratory drive is the highest ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons [105], oxytocin, via the allosteric RRI established in the heterocomplex, markedly increased D 2 receptor recognition (increased affinity of the high-affinity state) and increased the coupling of G i/o to the receptor. The D 2 -OTR heterodimer was recently identified in astrocytes as well [106], and the activation of OTR was shown to have a facilitatory effect on the response of D 2 receptors, causing them to be activated by subthreshold D 2 agonist concentrations and leading to an inhibition of glutamate release by the cells.…”
Section: Receptor Complexes Involving D 2 -Like Dopamine Receptorsmentioning
confidence: 99%
“…In this context, extensive available data indicate that RRIs may play a significant role. Relevant examples include the heterodimers A 2A -D 2 and D 2 -OTR [96,106], formed by the association of the dopamine D 2 receptor with the adenosine A 2A or the oxytocin receptor, respectively. These receptor complexes are present in astrocytes and regulate the release of glutamate from these cells [106,127], a process relevant for the control of glutamatergic transmission in striatum and with potential roles in the dysregulation of glutamatergic transmission in various neuropsychiatric diseases (see [176] for a specific review on this topic).…”
Section: Neuron-astrocyte Crosstalkmentioning
confidence: 99%